The overprescribing of opioids: a public health approach to an epidemic of addiction - Iram, Sadia; Haider, Abdullah (Journal of the Pakistan Medical Association, 2023)
Madam, Opioids a group of illegal drugs such as heroin, and analgesics available legally by prescription, including morphine. Opioids are very addictive as they induce euphoria and sedation, and upon the termination of chorionic use, patients can experience opioid withdrawal symptoms. Opioid crises are usually triggered by their overprescription as analgesics which can lead to diversion and misuse. The use of prescription opioid analgesics doubled between 2001-2013, with many countries affected by epidemics of opioid misuse during this period. In this context, overprescribing OPR’s (opioid related pain relievers) for post-surgical pain has been acknowledged as a noticeable public health concern and a potential contributor to the pattern of opioid misuse but this is ignored too.[1] From 1999-2011 oxycodone consumption increased by nearly 500% and hydrocodone almost doubled. Opioid misuse needs immediate attention to prevent national epidemics such as in the USA in these past two decades above five million opioid- related deaths have been reported, more than half of which involved prescription opioids.[2]. It has been observed that physicians prescribe opioids in more than half non-surgical hospital admissions, often in high doses. Postpartum opioid prescription is another contributing factor to the issue; approximately 80% of women are prescribed opioids after C-section and about 54% of women after normal delivery, although these figures vary in different regions. The risk of chronic opioid use related to opioid prescribing after birth may not seem high (Annual risk: 0.12-0.65%), but such a large number of women being exposed to opioids and those who become chronic users out of them per year is alarming.[3] In Pakistan, after cannabis, opiates and heroin are 2nd and 3rd most commonly used drugs, respectively.[4] Due to easy availability, opioid addiction is common, a survey showed approximately 1.6 million Pakistanis abusing prescription opioids for non-medical use.[5] The majority of the primary care physicians who prescribe opioids do not follow all the recommended approaches to reduce the occurrence of opioid overuse. According to the UNODC, Pakistan is among the top 10 countries with the highest rate of opioid addiction, with or without a prescription. In our country, the general physicians play a significant role, as opioids are routinely prescribed in OPD to manage acute and chronic pain. —Continue